LUMACO: MAPUCHE’S SELF-DETERMINIST MOVEMENT MADURATION - Pairicán Padilla, Fernando (Revista de Historia Social y de las Mentalidades, 2024)
On December 1st, 1997, three trucks owned by Forestal Arauco were completely burned. The incident shaked up all the Araucanía Region and generated a qualitative change in the politization of the mapuche people that had started in the beginning of the democratic transition. Lumaco defined a new stage in the mapuche movement and history, where the idea of a self-determination proyect appears more clearly. It whas the beginning of an ideological development for a sector of the mapuche people who defined their anti-capitalism as a central point of the movement, and symbolized the resistance in the irruption of the political violence as a resource to rebuild what they called Wallmapu.